European emission allowance and equity markets: evidence from further trading phases. Issue 3 (15th July 2019) - Harasheh, Murad; Amaduzzi, Andrea
Abstract : Purpose: This paper aims to investigate the value relevance of the European Emission Allowance (EUA) return and volatility on the equity value of the top listed European Power Generation Firms for the three trading phases of the European Emission Trading Scheme. Design/methodology/approach: The authors use the multifactor financial market model over the period 2005-2016 on daily basis for the return relevance relationship, whereas time series models such as autoregression moving average and generalized autoregressive conditional heteroskedasticity are applied on a weighted average portfolio of the sample firms to test serial correlation and volatility of returns. Findings: The findings are novel in which a positive and significant relevance of EUA return on equity return is shown; however, a vanishing effect is seen as one moves to further trading phases. Another remarkable finding is that the return relationship remains constant until a certain level in EUA price then inverts. Finally, the authors present that EUA is considered a systematic factor as firm and country-specific features are not statistically significant. Practical implications: At policy level, these findings signal policymakers for an appropriate design of the future trading phases in which they achieve the balance between public interests, as climate risk mitigation by reducing emissions, and the private interests of the market players to support innovative changes. Originality/value: To the authors' knowledge, this study would be the first to offer recent and comprehensive findings on the economic and financial implications of the European Emission Trading Scheme for the three trading phases. Additionally, the research offers time series robustness check besides the standard regression analysis and shows that there is an optimal EUA price that triggers polluters' decision on emission and generation.